Similarities and differences in cervical and thoracolumbar multisegmental motor responses and the combined use for testing spinal circuitries - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Study design: Experimental study. Objective: To determine similarities and differences of C7 and T11-12 multisegmental motor responses (MMR) studies for the upper limbs (UL) and lower limbs (LL). Settings: Neuroscience Lab, TWU (School of Physical Therapy, TX, USA). Methods: C7 and T11-12 percutaneous electrical stimulations were applied while recording muscle action potentials from ULs and LLs. Results: The procedure of cervical MMR (CMMR) was easier in application than thoracolumbar MMR (TMMR), requiring less current intensities but cause more jolts in the trapezius/shoulder complex, due to close proximity of the stimulation electrodes. CMMR evoked large amplitude motor responses in the millivolts range in (UL) muscles, but smaller amplitude signal in (LL) muscles (in microvolts). TMMR evoked large amplitude motor responses in both UL and LL (in millivolts). The MMR amplitude was generally larger in the UL as compared to the LL, in the distal limb muscles more than in the proximal limb muscles. CMMR and TMMR for the UL were comparable in amplitude, latencies and action potential shapes. Signal latencies were longer for distal limb muscles as compared to proximal limb muscles and were slightly longer for LL as compared to UL muscles. MMR signals were either biphasic or triphasic in shape. Conclusion: CMMR and TMMR have similarities and differences in the methods and recording signal that must be considered during its clinical applications. Comparing the signal of the UL muscles with CMMR and TMMR could be a useful test for the integrity of the ascending and descending spinal pathways in patients with spinal cord injuries and diseases.
Keywords: Multisegmental Motor Responses; Spinal Cord; Thoracic; Cervical; Propriospinal pathways; EPIDURAL STIMULATION; MUSCLE RESPONSES; LEG MUSCLES; CORD; MICROSTIMULATION; MODULATION; GENERATE; REFLEXES